Prevalence and factors associated with adherence to highly active anti-retroviral therapy among patients living with HIV and AIDS in a tertiary care unit in Kozhikode - Subbiah, Suthanthira Kannan; Reddy, Suganya Kuppovi; Thavody, Jayakrishnan; Bina, Thomas (International Journal Of Community Medicine And Public Health, 2020)
Background: Adherence to therapy is central to the success of anti-retroviral treatment (ART) and one of the most important factors influencing long term prognosis of HIV infection. In order to achieve this, patients are required to maintain more than 95% adherence to achieve lasting suppression of viral replication. The objective of the study was to assess the adherence to highly active antiretroviral therapy among people living with HIV (PLHIV) and the factors associated with adherence. Methods: This was a cross-sectional study conducted among PLHIV patients attending ART clinic, government medical college, Kozhikode from June 2015 to 2016. Adherence was estimated using modified Morisky 8 items questionnaire. Pretested semi-structured questionnaire was used to study various associated factors by interview method. Results: Of the 265 patients, the majority 246 (92.8%) were found to be treatment adherent and 19 (7.2%) were non-adherent. Most of the study population were in the age group 31-45 years and majority of the PLHIV were taking first line fixed dose regimens. Factors such as the early stage of the disease, using a method to remember, disclosure status, involvement in social activities, regular visit to ART clinic, financial and emotional support, involvement in social activities and HIV in the family were found be positively associated with adherence. Conclusions: Our study had found that a cordial environment in the ART centre will improve adherence and factors such as strong patient-provider relationship, including trust and engagement with the provider, which helps in improving ART adherence.